Synthesis of hybrid carbon nanotube structures coated with Sophora flavescens nanoparticles and their application to antimicrobial air filtration - Hwang, Gi Byoung; Sim, Kyoung Mi; Bae, Gwi-Nam; Jung, Jae Hee (ELSEVIER SCI LTD, 2015)
Controlling airborne microorganisms has become increasingly important with increase in human indoor activities, epidemic disease outbreaks, and airborne pathogen transmission. Treatments using antimicrobial nanoparticles have shown promise because of the high surface-to-volume ratio of nanoparticles compared to their bulk counterparts, and their unique physical and chemical properties. In this study, hybrid nanostructures of multi-walled carbon nanotubes (MWCNTs) coated with antimicrobial, natural product (NP) nanoparticles were synthesized using a twin-head electrospray system (THES). The coated nanoparticles were then used in antimicrobial air filters to increase their antimicrobial efficiency. Electrosprayed droplets were converted to NP nanoparticles and MWCNTs through ethanol evaporation. Oppositely charged NP nanoparticles and MWCNTs were coagulated via Coulombic collisions to form hybrid nanoparticles that were deposited continuously onto an air filter medium. The size distribution and composition of the hybrid NP/MWCNT particles were characterized using a wide-range particle spectrometer (WPS) and transmission electron microscope (TEM). The concentration of hybrid NP/MWCNT nanoparticles was lower than that of NP nanoparticles but higher than that of MWCNTs and showed a bimodal size distribution with peak diameters of 21.1 and 49 nm. TEM analyses confirmed that the NP nanoparticles were attached to the MWCNT surface with a density of similar to 4-9 particles/MWCNT. When deposited onto the filter medium, NP/MWCNT particles formed dendrites on the filter's fiber surface. The filtration efficiency and pressure drop of the NP/MWCNT-coated filters were higher than those of pristine, NP nanoparticles-coated or MWCNTs-coated filters. The hybrid filter also exhibited stronger antimicrobial activity than those of NP or MWCNT-coated filters at identical deposited volumes (1.1 x 10(-2) cm(3)/Cm-filter(2)). Ninety-five percent of the tested bacterial aerosols were inactivated on the NP/MWCNTs filter while only <70% were inactivated on NP- or MWCNT-coated filters. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: TWIN-HEAD ELECTROSPRAY; SILVER NANOPARTICLES; BIPOLAR COAGULATION; ESCHERICHIA-COLI; MU-M; ANTIBACTERIAL; INACTIVATION; PARTICLES; BIOAEROSOLS; DROPLETS